The Neomycin Resistance Cassette in the Targeted Allele of Shank3B Knock-Out Mice Has Potential Off-Target Effects to Produce an Unusual Shank3 Isoform - Jin, Chunmei; Kang, Hyojin; Yoo, Taesun; Ryu, Jae Ryun; Yoo, Ye-Eun; Ma, Ruiying; Zhang, Yinhua; Kang, Hyae Rim; Kim, Yoonhee; Seong, Hyunyoung; Bang, Geul; Park, Sangwoo; et al. (Frontiers in Molecular Neuroscience, 2021)
Variants of the SH3 and multiple ankyrin repeat domains 3 (SHANK3), which encodes postsynaptic scaffolds, are associated with brain disorders. The targeted alleles in a few Shank3 knock-out (KO) lines contain a neomycin resistance (Neo) cassette, which may perturb the normal expression of neighboring genes; however, this has not been investigated in detail. We previously reported an unexpected increase in the mRNA expression of Shank3 exons 1–12 in the brains of Shank3B KO mice generated by replacing Shank3 exons 13–16 with the Neo cassette. In this study, we confirmed that the increased Shank3 mRNA in Shank3B KO brains produced an unusual ~60 kDa Shank3 isoform (Shank3-N), which did not properly localize to the synaptic compartment. Functionally, Shank3-N overexpression altered the dendritic spine morphology in cultured neurons. Importantly, Shank3-N expression in Shank3B KO mice was not a compensatory response to a reduction of full-length Shank3 because expression was still detected in the brain after normalizing the level of full-length Shank3. Moreover, in another Shank3 KO line (Shank3 gKO) with a similar Shank3 exonal deletion as that in Shank3B KO mice but without a Neo cassette, the mRNA expression levels of Shank3 exons 1–12 were lower than those of wild-type mice and Shank3-N was not detected in the brain. In addition, the expression levels of genes neighboring Shank3 on chromosome 15 were altered in the striatum of Shank3B KO but not Shank3 gKO mice. These results suggest that the Neo cassette has potential off-target effects in Shank3B KO mice.